THE EFFECT OF LEVERAGE ON PROFITABILITY WITH FIRM VALUE AS A MODERATING VARIABLE IN INVESTMENT COMPANY SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2014-2024 - Iin Syofia Yandra; Zachari Abdallah; Nurapni Jami Putri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to determine the Effect of Leverage on Profitability with Company Value as a Moderating Variablein Investment Company Sub Sector Companies listed on the Indonesia Stock Exchange in 2014-2024. The Dependen Variable is this Study is Profitability, the Independen Variable is Leverage while Moderation is Company Value. The pupolation in the study is 11 companies from 2014-2024. Only 1 company meet the criteria, so the data used is 10 data. The results of this study prove that partially Leverage does not have a significant effect on Profitability. Simultaneously, the Leverage and Company Value variables have a significant effect on Profitability. The Application of Company Value does not moderate Leverage on Profitability.